2017
DOI: 10.1016/j.ram.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of honey from the Pampas Region (Argentina) throughout the extraction process

Abstract: The microbiological quality of honey obtained from different processing points and the environmental quality within honey houses were assessed in the Pampas Region (Argentina). Mold and yeast (MY), culturable heterotrophic mesophilic bacteria (CHMB), the number of spore-forming bacteria as well as the presence of Shigella spp., Salmonella spp. and fecal coliforms were evaluated in 163 samples. These samples were taken from eight honey houses. Results showed that 89 samples had ≤10CFU of MY/g honey, 69 ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
4
15
1
Order By: Relevance
“…The secondary sources are those arising from the honey manipulation by people, thus are closely connected with hygiene of processing, handling, and storage [11]. Such sources includes skin, mouth, and nose of food handlers, equipment, buildings as well as cross-contamination during harvest and processing in honey houses, however, they can be easy control by the application of good manufacturing practices [14],[15]. Microorganisms found in honey must demonstrate the ability to withstand the concentrated sugar, acidity and other severe conditions, thus in most cases they are present in latent forms (dormant) such as spores [4].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary sources are those arising from the honey manipulation by people, thus are closely connected with hygiene of processing, handling, and storage [11]. Such sources includes skin, mouth, and nose of food handlers, equipment, buildings as well as cross-contamination during harvest and processing in honey houses, however, they can be easy control by the application of good manufacturing practices [14],[15]. Microorganisms found in honey must demonstrate the ability to withstand the concentrated sugar, acidity and other severe conditions, thus in most cases they are present in latent forms (dormant) such as spores [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the Polish honey samples contained up to 20% of water, which is in line with EU Directive [21]. This limit was exceeded in four Polish samples (P1, P3, P8 and P16) and in the thirteen samples of Thai honeys, which indicates the unripe of Thai honeys [17,21,27].…”
Section: Discussionmentioning
confidence: 62%
“…Piana et al, 1991 reported yeast growth only in honey samples with a water activity < 0.65 [38]. The presence of yeasts and molds is also often caused by cross-contamination from product handling equipment [17].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that the microbial quality of extracted honey is relatively lower than that of comb honey. In a study that analyzed honey samples from different points of a honey processing unit was reported that postharvest extracted honey contained increased numbers of TMAB, yeasts and molds, and that coliform bacteria, was not detected in comb honey (Fernandez et al, 2017). In their study on the comparison of the cold and hot extraction methods used to obtain extracted honey from comb honey, Gallez and Fernández (2009) determined that the microbial contamination of extracted honey occurred with the use of both methods and the cold extraction method posed a greater risk of contamination than the hot extraction method.…”
Section: Discussionmentioning
confidence: 99%